2022
DOI: 10.1186/s43055-022-00814-z
|View full text |Cite
|
Sign up to set email alerts
|

Role of prenatal fetal echocardiography in the assessment of intrauterine growth restriction

Abstract: Background Intrauterine growth restriction (IUGR) is a common diagnosis in obstetrics and carries an increased risk of perinatal mortality and morbidity. Identification of IUGR is crucial because proper evaluation and management can result in a favourable outcome. Cardiovascular dysfunction and remodelling is a central feature of IUGR. The aim of the study was to use the left modified myocardial performance index (MPI), assess cardiac function in foetuses with intrauterine growth restriction (I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(7 citation statements)
references
References 12 publications
6
1
0
Order By: Relevance
“…Those outcomes agreed with Öcal et al (7) who studied forty females had growth-restricted fetuses and forty females had fetuses of normal weight (controls) at 29-39 gestational weeks. Also, this is in accordance with Nguyen et al (8) and Ali et al (15) . It is also, in agreement with Şimşek and Köse (4) who reported that no statistically significant variance was noted.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…Those outcomes agreed with Öcal et al (7) who studied forty females had growth-restricted fetuses and forty females had fetuses of normal weight (controls) at 29-39 gestational weeks. Also, this is in accordance with Nguyen et al (8) and Ali et al (15) . It is also, in agreement with Şimşek and Köse (4) who reported that no statistically significant variance was noted.…”
Section: Discussionsupporting
confidence: 93%
“…That was in concurrence with Eslamian et al (17) who stated that MPI was 0.4 ± 0.1 and 0.3 ± 0.1 in case and control groups, correspondingly, which was significantly variant among the both groups (P < 0.001). Also, this is in accordance with Ali et al (15) who stated that the average cardiac PI was 0.58 ± 0.02 in the group with IUGR, whereas in the control group, it was 0.44 ± 0.01. The observed outcome was highly statistically significant, with a p-value of less than 0.001.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations